AB0841 Articular manifestations of antisynthetase syndrome: A retrospective study of 22 patients. (23rd January 2014) - Nunokawa, T.; Sugii, S.; Shimada, K.; Yokogawa, N.; Nakashima, R.; Hosono, Y.; Sato, S.; Suzuki, Y.; Chinen, N.
Abstract : Background: Antisynthetase syndrome is associated with anti-aminoacyl-tRNA antibodies and often presents with inflammatory myopathy, interstitial lung disease and polyarthritis, which may mimic rheumatoid arthritis or erosive osteoarthritis. Objectives: The aim of this study is to evaluate articular manifestations of antisynthetase syndrome based on the types of antibodies. Methods: Clinical and radiological features of patients with antisynthetase syndrome were reviewed using electric chart system at our hospital. Results: Twenty-two patients were diagnosed as antisynthetase syndrome associated with 5 types of anti-aminoacyl-tRNA antibodies: anti-Jo-1 10, anti-EJ 8, anti-PL-7 2, anti-KS 1, anti-OJ. Fifteen patients (68%) had arthralgia and/or arthritis. While only two patients with anti-EJ had articular involvement, all of the patients with anti-Jo 1 and three with other antibodies had. In hand X-rays, joint deformities, most frequently subluxations, were found in five patients with anti-Jo 1 and one with anti-PL 7. DIP involvement was observed in four patients, PIP in two, MCP in one. On MRI of four patients, tenosynovitis was prominent compared to bone erosion or edema. One patient presented marked periarticular calcinosis. Conclusions: Anti-Jo-1 antibody exhibited more severe articular manifestations than other antibodies. Subclinical tenosynovitis may potentiate a progressive joint deformity, such as DIP subluxation. References: Oddis CV et al, A subluxing arthropathy associated with the anti-Jo-1 antibody in polymyositis/dermatomyositis, 1990, Arthritis Rheum 33:1640-5 Meyer O et al, Subluxing arthropathy: an unusual manifestation of the antisynthetase syndrome, 2009, Ann Rheum Dis 68:152-3 Disclosure of Interest: None Declared